A Conserved Organization of Transcription during Embryonic Stem Cell Differentiation and in Cells with High C Value - Faro-Trindade, Inês (The American Society for Cell Biology, 2006)
Although we have detailed information on the alterations occurring in steady-state levels of all cellular mRNAs during differentiation, we still know little about more global changes. Therefore, we investigated the numbers of molecules of RNA polymerase II that are active—and the way those molecules are organized—as two mouse cells (aneuploid F9 teratocarcinoma, and euploid and totipotent embryonic stem cells) differentiate into parietal endoderm. Quantitative immunoblotting shows the number of active molecules roughly halves. Transcription sites (detected by light and electron microscopy after allowing engaged polymerases to extend nascent transcripts in bromouridine-triphosphate) are uniformly distributed throughout the nucleoplasm. The numbers of such sites fall during differentiation as nuclei become smaller, but site density and diameter remain roughly constant. Similar site densities and diameters are found in salamander (amphibian) cells with 11-fold larger genomes, and in aneuploid HeLa cells. We conclude that active polymerases and their nascent transcripts are concentrated in a limited number of discrete nucleoplasmic sites or factories, and we speculate that the organization of transcription is conserved during both differentiation and evolution to a high C value.